Electrokinetic removal of mixed heavy metals from a contaminated low permeable soil by surfactant and chelants - Paramkusam B.R.; Srivastava R.K.; Mohan D. (My University, 2025)
This paper presents the experimental findings of electrokinetic (EK) studies conducted to remove cadmium (Cd++) and copper (Cu++) present together as contaminants in clayey soil. Competitive sorption between cadmium and copper has been studied, which provides an insight into selection of Cd++ and Cu++ concentrations for maximum contamination of soil in the EK study. To explore the effect of pH on the desorption of both Cd++ and Cu++ and to compare the efficacy of different agents in enhancing the removal of these ions during the EK remediation process, the desorption studies have also been conducted using ammonium citrate (1 M), sodium citrate (1 M) and non-ionic surfactant Tween-20 (0.2 % v/v) at pH 2, pH 7, and pH 12. It was found that maximal sorption capacity of the soil for Cd++ and Cu++ was 8.34 and 12.1 mg g−1, respectively. The desorption of both Cd++ and Cu++ influenced by pH for all desorbing agents is considered in the study. Overall desorption values for both Cd++ and Cu++ have been observed to be higher when ammonium citrate (1 M) was used as desorbing agent in the study. The results indicate the possibility of competition of complexation of Cd++ and Cu++ leading to desorption mechanism in the presence of desorbing agents. The EK tests on the Cd++ and Cu++ contaminated soil are carried out at a voltage of 35 V (1.0 V/cm) DC for 5 days. Sequential extraction experiments were conducted to determine fractionation of Cd++ and Cu++ in the EK-treated soil using deionized water at pH values of 2, 7 and 12. It is observed that current, electroosmotic flow and mobilization of Cd++ and Cu++ depend on pH, zeta potential (ς) and specific conductance. Removal of these heavy metals was observed to be higher when ammonium citrate was used both for saturation as well as flushing solution during EK process. © 2014, Springer-Verlag Berlin Heidelberg.